INTEGRATION OF QUALITY FUNCTION DEPLOYMENT, TARGET COSTING AND VALUE ENGINEERING TO IMPROVE PRODUCT VALUE (APPLIED RESEARCH IN THE STATE COMPANY FOR TEXTILE INDUSTRIES/ HILLA TEXTILE FACTORY) - Husam Muhammed Ali Alawaed (Scholar Express Journals, 2022)
The research aims to demonstrate the impact of the publication of the quality function, target cost and value engineering in improving the value of the product. As the quality function publication tool works to identify the requirements of customers and arrange them according to priorities, the target cost works to determine the costs of competing products and the value engineering works to determine the cost of each function of the product and to know the job that adds value and the job that does not add value to remove the job that does not add value to the customer, and the researcher reached To a number of conclusions, the most important of which is the presence of untapped human energies and resources, as well as the decrease in the company’s production volume is mainly due to the technological obsolescence of the machines that have passed many years and have not been replaced
Keywords: Quality Function Deployment; Target Costing; Value Engineering